Evaluating Eucalyptus leaf colonization by Brasilonema octagenarum (Cyanobacteria, Scytonemataceae) using in planta experiments and genomics - Alvarenga, Danillo O. [UNESP]; Franco, Maione W.; Sivonen, Kaarina; Fiore, Marli F.; Varani, Alessandro M. [UNESP] (PeerJ, 2020)
Background. Brasilonema is a cyanobacterial genus found on the surface of mineral substrates and plants such as bromeliads, orchids and eucalyptus. B. octagenarum stands out among cyanobacteria due to causing damage to the leaves of its host in an interaction not yet observed in other cyanobacteria. Previous studies revealed that B. octagenaum UFV-E1 is capable of leading eucalyptus leaves to suffer internal tissue damage and necrosis by unknown mechanisms. This work aimed to investigate the effects of B. octagenarum UFV-E1 inoculation on Eucalyptus urograndis and to uncover molecular mechanisms potentially involved in leaf damage by these cyanobacteria using a comparative genomics approach. Results. Leaves from E. urograndis saplings were exposed for 30 days to B. octagenarum UFV-E1, which was followed by the characterization of its genome and its comparison with the genomes of four other Brasilonema strains isolated from phyllosphere and the surface of mineral substrates. While UFV-E1 inoculation caused an increase in root and stem dry mass of the host plants, the sites colonized by cyanobacteria on leaves presented a significant decrease in pigmentation, showing that the cyanobacterial mats have an effect on leaf cell structure. Genomic analyses revealed that all evaluated Brasilonema genomes harbored genes encoding molecules possibly involved in plant-pathogen interactions, such as hydrolases targeting plant cell walls and proteins similar to known virulence factors from plant pathogens. However, sequences related to the type III secretory system and effectors were not detected, suggesting that, even if any virulence factors could be expressed in contact with their hosts, they would not have the structural means to actively reach plant cytoplasm. Conclusions. Leaf damage by this species is likely related to the blockage of access to sunlight by the efficient growth of cyanobacterial mats on the phyllosphere, which may hinder the photosynthetic machinery and prevent access to some essential molecules. These results reveal that the presence of cyanobacteria on leaf surfaces is not as universally beneficial as previously thought, since they may not merely provide the products of nitrogen fixation to their hosts in exchange for physical support, but in some cases also hinder regular leaf physiology leading to tissue damage.
Keywords: Cyanobacteriota; Horizontal gene transfer; Lignocellulolytic enzymes; Oxyphotobacteria; Phyllosphere; Virulence factors